IMPACT OF THE BOARD OF DIRECTORS' FINANCIAL EXPERTISE ON CORPORATE FINANCIAL SUSTAINABILITY: THE ROLE OF FEMALE REPRESENTATION (World Economics and Finance Bulletin, 2026)
The research aims to test the impact of accounting and financial expertise and female representation in financial sustainability, and the research in the analysis was based on the financial reports of a sample of companies listed on the Iraq Stock Exchange amounted to (10) banks for the period 2013- 2023, and it was concluded that the accounting and financial expertise and female representation on the board of directors does not affect and is not related to the financial sustainability of the companies sample study, and as for the size of the board of directors, we have found that there is a positive impact of the board of directors in financial sustainability, which means that large boards of directors contribute to drawing policies and making financial decisions that have an impact on the wealth of the company and its sustainability. The research recommends the need to comply with local and international governance controls because of their role in the growth and sustainability of companies and emphasize the need to support the demographic diversity of the board of directors.
Keywords: Financial sustainability; Financial expertise; Characteristics of board of directors